Pengaruh Pasang Surut terhadap Pengendapan Lumpur di Lahan Sawah Rawa Kawasan Sungai Barito Kalimantan Selatan - M Mawardi; Putu Sudira; Bambang Hendro Sunarminto; Totok Gunawan; Benito Hadi Purwanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Swamp land has a great potential to be developed as a paddy field area. However it has many constraints such as-phyrite (FeS2) at the depth of 30–60 cm and lack of soil nutrition. On the other hand, supply of marine clay from the sea which contains a lot of smektit clay mineral can be used to netralize this condition. Mud clay is very important for the development of rice root because it contains much nutrition and to enlarge the top of soil reducing the oxidation of phyrite. This study was conducted from January 2016 to June 2017 in swamp land area of Barito River of South Kalimantan. Data was collected by measuring the difference between maximum and minimum sea tide (tidal amplitude) and the deposition of mud clay. The results indicated that the distribution of mud clay deposit vary depends on the geography and the tidal amplitude of the zone. Zone VII has higher concenration of mud clay than the other one. The distribution pattern of mud clay deposit follows the parabola type, verticaly and horizontaly type, as well. Increasing of mud clay at all of the zone areas are not significantly effected by the daily tidal amplitude, only depends on climate condition/the season change.